Frequency of Proteinuria in Newly Diagnosed Diabetic Patients - Adnan Rahman, Bakht Babar, Ali Sebtain, Hira Gul, Muhammad Qasim, Syed Hassan Mustafa, Mahnoor, Irfan Ullah (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Diabetes mellitus is a huge global health issue, affecting more than 350 million people worldwide, and the number might rise to 439 million in 2030. Diabetes Mellitus is associated with many complications. Most of these complications usually develop after many years or even decades of exposure to chronic hyperglycemia. Diabetic Nephropathy is one of the most common and grave complication of diabetes mellitus and is associated with increased morbidity and mortality. Study Design: A cross-sectional study was performed on 285 patients from August 2021 to February 2022 on all newly diabetic patients in Hayatabad Medical Complex, Peshawar. Their 24-hour urine for protein analysis was measured to screen them for proteinuria.After measuring the urine protein level in each patient, the study’s total frequency was computed across all the patients who had been diagnosed. Data was recorded into a proforma. Results: The age range in this study was from 15 to 70 years with a mean age of 43.01±6.90 years, mean BMI was 27.67±1.99 Kg/m2, and mean proteinuria levels were 42.38±34.142mg/ dl. Males constituted the majority of the patient-group (62.1%). 34.7% of patients were also hypertensive. Proteinuria was seen in 114 patients (40%). Conclusion: This study has concluded that screening for the complications of diabetic patients is beneficial in the preventive management of the disease. Keywords: Diabetic patients, proteinuria